X-ray detector based on formamidinium calcium perovskite single crystal and preparation thereof
Patent Information
- Application Number
- CN202311424298.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-10-31
AI Technical Summary
然而,目前基于钙钛矿的X射线探测器存在着暗电流大、探测器噪声大、稳定性差以及难以与硅基电路结合等问题,距离X射线探测器的实际应用还存在较大差距
[0018]本发明通过掺杂少量GAI,改进Cs0.1FA0.9Pb(I0.9Br0.1)3的A位阳离子组分,得到性能更优的Cs0.1FA0.85GA0.05Pb(I0.9Br0.1)3,其是在提前制备的钙钛矿前驱体溶液中,通过缓慢升温的方法先制备籽晶,之后挑选形状规则的籽晶转移至新配置的前驱体溶液中进行继续生长,直至大小合适,完成单晶晶体的生长。接着将提前制备的PCBM:C60(1:1摩尔比)溶液通过滴涂的方式制备PCBM:C60传输层,最后通过蒸镀的方式制备MoO3传输层、Au电极、BCP传输层和Cu电极,完成钙钛矿单晶X射线探测器的制备,所制备的X射线探测器具有暗电流低、噪声低、灵敏度高、检测下限低等优点。
Smart Images

Figure CN117337116B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite optoelectronic device technology, specifically relating to an X-ray detector based on a dopant-based formamidinium perovskite single crystal and its fabrication method. Background Technology
[0002] Since the discovery of X-rays, they have been widely applied in numerous fields such as medicine, geology, and cultural relic preservation. X-ray detection technology includes direct and indirect detection. A typical X-ray detector consists of a detection material (such as a scintillator), a photoelectric conversion array, and a circuit. The photoelectric conversion array and circuit together constitute a photoelectric sensor. Generally, the linear dynamic range, response speed, spectral sensitivity, color accuracy, and resolution of a photoelectric sensor are primarily determined by the detection material; therefore, the detection material largely determines the imaging quality of the photoelectric sensor. To date, most commercial digital sensors, such as charge-coupled devices (CCDs) and complementary metal-oxide-semiconductor (CMOS) devices, are typically based on amorphous silicon or crystalline silicon (Si). Although the performance of Si-based photoelectric sensors has been proven, they still suffer from drawbacks such as low carrier mobility and poor photoresponse performance.
[0003] Organic-inorganic lead halide perovskites have become a global research hotspot in recent years due to their advantages of simple preparation and high photoelectric conversion efficiency, particularly in fields such as perovskite solar cells. They are also considered a novel semiconductor material suitable for X-ray detection. The two most common forms of perovskite materials in optoelectronic applications are polycrystalline thin films and single-crystal structures. However, polycrystalline thin films suffer from numerous defects, severely impacting device performance. Meanwhile, single crystals exhibit better performance than polycrystalline thin films due to the elimination of grain boundaries. However, current perovskite-based X-ray detectors suffer from problems such as high dark current, high detector noise, poor stability, and difficulty in integrating with silicon-based circuits, leaving a significant gap before practical application. Therefore, preparing higher-quality perovskite single crystals is considered a key issue for the practical application of X-ray detectors. Summary of the Invention
[0004] The purpose of this invention is to provide a formamidinium perovskite single-crystal X-ray detector based on the action of a dopant (guanidine iodide GAI) and its fabrication method. This invention is based on Cs 0.1 FA 0.9 Pb(I 0.9 Br 0.1 )3 Single crystals are doped at the A-site to obtain Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1)3 Perovskite single crystals have the advantages of simple growth methods and regular morphology. The X-ray detectors prepared from them have the characteristics of low dark current, low noise, high sensitivity and low detection limit.
[0005] This invention is achieved through the following technical solution:
[0006] An X-ray detector based on dopant-based formamidinium perovskite single crystal, the device structure consisting of an Au electrode, a MoO3 transport layer, a perovskite single crystal, and a PCBM:C 60 The device consists of a transport layer, a BCP transport layer, and Cu electrodes. The perovskite single crystal material used in the device is Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3. The detector is prepared by the following steps:
[0007] I. Preparation of GAI-doped formamidinium perovskite single crystals
[0008] 1) Preparation of Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3. Solution: A mixture of FAI, PbI2, PbBr2, CsI, and GAI (CH5N3·HI) solid powders in a molar ratio of 17:17:3:2:1 was dissolved in 1–2 mL of γ-butyrolactone. The mixture was then magnetically stirred at room temperature until the perovskite material was completely dissolved, yielding a CsI solution with a concentration of 0.5–2 mol / L. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite precursor solution;
[0009] 2) Seed crystal growth: The Cs obtained in step 1) 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. After heating the perovskite precursor solution, maintain the temperature for a period of time until black perovskite seed crystals are formed in the solution.
[0010] 3) Single crystal growth: The perovskite seed crystal with a relatively regular shape (regular hexagonal structure, with side lengths of approximately 0.1 cm on the top and bottom surfaces and a thickness of approximately 0.05 cm) obtained in step 2) is transferred into the newly prepared and preheated Cs crystal as described in step 1). 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br0.1 3. In the perovskite precursor solution, the temperature is increased from the initial temperature of 60-65℃ for 15-30 hours to continue crystal growth, thereby obtaining Cs crystals with regular shape and appropriate size (regular hexagonal structure, with side lengths of 0.4-0.6 cm on the upper and lower surfaces and a thickness of 0.2-0.3 cm). 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite single crystal;
[0011] Furthermore, the stirring time in step 1) is 8–12 hours;
[0012] Furthermore, in step 2), Cs is... 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Heat the solution to 80-85℃;
[0013] Furthermore, the heating rate in step 3) is 0.25–0.75 °C / h.
[0014] II. Fabrication of GAI-doped formamidinium perovskite single-crystal X-ray detectors
[0015] Prepared Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. The perovskite single crystal is subjected to ozone passivation treatment for 10-15 minutes on one side; then, it is transferred to a nitrogen glove box, and 60-70 μL of PCBM is added dropwise to the ozone passivation side each time. 60 A 1:1 molar ratio solution (dichlorobenzene as solvent, with PCBM concentration ranging from 15 to 30 mg / mL) was added dropwise 3 to 5 times; after the drop coating was completed, the perovskite single crystal was annealed on a hot stage at 90–110 °C for 0.5–2.0 h; finally, physical vapor deposition was used to deposit PCBM:C 60 A BCP transport layer and a Cu electrode are sequentially deposited on the transport layer, and a MoO3 transport layer and an Au electrode are sequentially deposited on the other side of the perovskite single crystal, thus obtaining an X-ray detector based on a perovskite single crystal.
[0016] Furthermore, the thickness of the BCP transport layer is 8–10 nm, the thickness of the Cu electrode is 80–100 nm, the thickness of the MoO3 transport layer is 20–30 nm, and the thickness of the Au electrode is 18–22 nm.
[0017] Compared with existing technologies, the advantages of this invention are as follows:
[0018] This invention improves Cs by doping with a small amount of GAI. 0.1 FA 0.9 Pb(I 0.9 Br 0.1 The A-site cation component of )3 yields Cs with superior performance. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. In this method, seed crystals are first prepared in a pre-prepared perovskite precursor solution by slowly increasing the temperature. Then, regularly shaped seed crystals are selected and transferred to a newly prepared precursor solution for continued growth until the desired size is achieved, completing the growth of a single crystal. Next, the pre-prepared PCBM:C 60 PCBM:C was prepared by drop-coating of a (1:1 molar ratio) solution. 60 The transport layer is then prepared by vapor deposition, and finally, the MoO3 transport layer, Au electrode, BCP transport layer and Cu electrode are prepared to complete the fabrication of the perovskite single crystal X-ray detector. The prepared X-ray detector has the advantages of low dark current, low noise, high sensitivity and low detection limit. Attached Figure Description
[0019] Figure 1 Cs prepared in Example 4 of this invention 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Optical photographs of perovskite single crystals, showing a relatively regular shape with a surface edge length of 0.4–0.6 cm and a thickness of 0.2–0.3 cm;
[0020] Figure 2 The above images show the X-ray diffraction (XRD) patterns of the perovskite single crystals prepared in Examples 1 and 4 of this invention. The upper spectrum (CsFA) is a Cs... 0.1 FA 0.9 Pb(I 0.9 Br 0.1 3) Perovskite single crystal, the spectrum below (CsFAGA) is Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3. Perovskite single crystals. X-ray diffraction peaks show no significant change in the peak positions of the perovskite single crystal powder before and after GAI doping optimization, proving that low-dose doping does not affect Cs. 0.1 FA 0.9 Pb(I 0.9 Br 0.1)3. It affects the stability of the crystal structure of perovskite single crystals;
[0021] Figure 3 Cs prepared in Example 4 of this invention 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Photoluminescence spectrum (PL) of perovskite single crystal, from which it can be seen that Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Perovskite single crystals can absorb light in a limited manner at a wavelength of 782nm;
[0022] Figure 4 Cs prepared in Example 4 of this invention 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Time-resolved photoluminescence spectrum (TRPL) of perovskite single crystal. According to calculations, Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 The lifetime of a perovskite single crystal is 432 ns.
[0023] Figure 5 This is a schematic diagram of the perovskite X-ray detector prepared in Example 4 of the present invention, where 1 is a Cu electrode, 2 is a BCP transport layer, and 3 is a PCBM:C 60 Transport layer, 4 is Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3 is a perovskite single crystal, 5 is a MoO3 transport layer, and 6 is an Au electrode;
[0024] Figure 6 The figure shows the short-circuit current density-voltage characteristic curve of the perovskite X-ray detector prepared in Example 4 of this invention under dark conditions. A clear rectification characteristic can be observed, with the dark current density reaching 1.1 × 10⁻⁶ at -5V. -8 A cm -2 ;
[0025] Figure 7The graph shows the external quantum efficiency of the perovskite X-ray detector prepared in Example 4 of this invention in the wavelength range of 500 nm to 900 nm. It can be seen that the external quantum efficiency of the device can reach 15% in its absorption band (782 nm).
[0026] Figure 8 The figure shows the noise current curve of the perovskite X-ray detector prepared in Example 4 of this invention. As can be seen from the figure, the noise current of the device prepared using this method at 100Hz is 3.8 × 10⁻⁶. -13 A, this is related to the low defect density of the device;
[0027] Figure 9 The figure shows the sensitivity curve of the perovskite X-ray detector prepared in Example 4 of this invention. As can be seen from the figure, based on Cs... 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite single-crystal X-ray detector at 25 V·cm -1 In this case, (7.7±0.1)×10 was achieved. 3 μC Gy air -1 cm -2 Its excellent sensitivity characteristics;
[0028] Figure 10 The figure shows the relationship between the photocurrent density and the X-ray dose rate of the perovskite X-ray detector prepared in Example 4 of this invention under X-ray irradiation. As can be seen from the figure, under the same electric field conditions, the signal current increases linearly with the increase of X-ray dose. Detailed Implementation
[0029] The following description, in conjunction with the accompanying drawings, relates to Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. The specific implementation plan for the perovskite single crystal X-ray detector is described in detail.
[0030] Example 1:
[0031] The method for fabricating a perovskite single-crystal X-ray detector provided by this invention includes the following steps:
[0032] 1. Clean the 5mL glass vial and magnetic stir bar sequentially with acetone, ethanol and deionized water using ultrasonic cleaning for 20min, and then dry them in an oven at 70℃ for 3.5h to obtain a dry and clean glass vial and magnetic stir bar.
[0033] 2. At room temperature, weigh out solid powders of FAI, PbI2, PbBr2 and CsI in a molar ratio of 18:17:3:2 and add them to a sealed glass vial; the molar amount of FAI is 1.8 mmol.
[0034] 3. Add 2 mL of γ-butyrolactone (GBL) solvent to the glass vial from step 2, and place a magnetic stir bar inside.
[0035] 4. At room temperature, weigh out PCBM and C in a molar ratio of 1:1. 60 The solid powder was added to another sealed glass vial; the amount of PCBM used was 20 mg.
[0036] 5. Add 1 mL of dichlorobenzene (DCB) solvent to the glass vial from step 4, and place a magnetic stir bar inside.
[0037] 6. Place the glass vials from steps 3 and 5 on a magnetic stirring table in a nitrogen glove box and stir at room temperature for 12 hours until all the solute is dissolved to obtain 1 mol / L Cs. 0.1 FA 0.9 Pb(I 0.9 Br 0.1 ) 33 Precursor solution and 20 mg / mL PCBM: C 60 Solution;
[0038] 7. Cs 0.1 FA 0.9 Pb(I 0.9 Br 0.1 )3 The precursor solution was placed on a preheated hot plate (75°C) and left to stand for 2 hours until black perovskite seed crystals grew in the solution.
[0039] 8. Select small seed crystals with regular shape and both upper and lower surfaces being regular hexagons (approximately 0.1cm in side length and 0.05cm in thickness), and transfer them to the newly configured Cs. 0.1 FA 0.9 Pb(I 0.9 Br 0.1 3. The precursor solution was placed in a preheated hot plate (60℃) and heated at a rate of 0.5℃ / h for 25h until Cs with regular shape and regular hexagonal shape on both the upper and lower surfaces (approximately 0.6cm side length and 0.3cm thickness) were grown. 0.1 FA 0.9 Pb(I 0.9 Br 0.1 )3 Perovskite single crystal;
[0040] 9. Transfer the grown Cs 0.1 FA0.9 Pb(I 0.9 Br 0.1 )3. Remove the perovskite single crystal from the glass bottle and subject the upper surface of the single crystal to ozone passivation treatment for 15 minutes.
[0041] 10. Transfer it to a nitrogen glove box, and add 65 μL of PCBM:C dropwise to the single-crystal ozone passivation treatment side each time. 60 The (1:1 molar ratio) solution was added dropwise 4 times. After the drop coating was completed, it was placed on a hot plate at 100°C for annealing for 1 hour.
[0042] 11. Using physical vapor deposition (PVD) on PCBM: C 60 A BCP transport layer and a Cu electrode are deposited on one side of the single crystal, and a MoO3 transport layer and an Au electrode are deposited on the other side, thus obtaining an X-ray detector based on a perovskite single crystal. The thickness of the BCP transport layer is 8 nm, the thickness of the Cu electrode is 90 nm, the thickness of the MoO3 transport layer is 25 nm, and the thickness of the Au electrode is 20 nm.
[0043] Example 2:
[0044] The method for fabricating a perovskite single-crystal X-ray detector provided by this invention includes the following steps:
[0045] 1. Clean the 5mL glass vial and magnetic stir bar sequentially with acetone, ethanol and deionized water using ultrasonic cleaning for 20min, and then dry them in an oven at 70℃ for 3.5h to obtain a dry and clean glass vial and magnetic stir bar.
[0046] 2. At room temperature, weigh out solid powders of FAI, PbI2, PbBr2, CsI and GAI in a molar ratio of 17:17:3:2:1 and add them to a sealed glass vial; the molar amount of FAI is 1.7 mmol.
[0047] 3. Add 2 mL of γ-butyrolactone (GBL) solvent to the glass vial from step 2, and place a magnetic stir bar inside.
[0048] 4. Place the glass vial from step 3 on a magnetic stirrer in a nitrogen glove box and stir at room temperature for 12 hours until all the solute is dissolved to obtain 1 mol / L Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 ) 33 Precursor solution;
[0049] 5. Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br0.1 )3. The precursor solution was placed on a preheated hot plate (80°C) and left to stand for 2 hours until black perovskite seed crystals grew in the solution.
[0050] 6. Select small seed crystals with regular shape and both upper and lower surfaces being regular hexagons (approximately 0.1cm in side length and 0.05cm in thickness), and transfer them to the newly configured Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3. The precursor solution was placed in a preheated hot plate (65℃) and heated at a rate of 0.5℃ / h for 25h until Cs with regular shape and regular hexagonal shape on both the upper and lower surfaces (side length of the upper and lower surfaces is about 0.6cm and thickness is about 0.3cm) grew. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite single crystal;
[0051] 7. Transfer the grown Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Remove the perovskite single crystal from the glass bottle and subject the upper surface of the single crystal to ozone passivation treatment for 15 minutes.
[0052] 8. C is deposited on the ozone passivation side of the single crystal using physical vapor deposition. 60 A transport layer, a BCP transport layer, and a Cu electrode are combined, and an Au electrode is deposited on the other side of the single crystal to obtain an X-ray detector based on a perovskite single crystal. 60 The thickness of the transport layer is 20 nm, the thickness of the BCP transport layer is 8 nm, the thickness of the Cu electrode is 90 nm, and the thickness of the Au electrode is 20 nm.
[0053] Example 3:
[0054] The method for fabricating a perovskite single-crystal X-ray detector provided by this invention includes the following steps:
[0055] 1. Clean the 5mL glass vial and magnetic stir bar sequentially with acetone, ethanol and deionized water using ultrasonic cleaning for 20min, and then dry them in an oven at 70℃ for 3.5h to obtain a dry and clean glass vial and magnetic stir bar.
[0056] 2. At room temperature, weigh out solid powders of FAI, PbI2, PbBr2, CsI and GAI in a molar ratio of 17:17:3:2:1 and add them to a sealed glass vial; the molar amount of FAI is 1.7 mmol.
[0057] 3. Add 2 mL of γ-butyrolactone (GBL) solvent to the glass vial from step 2, and place a magnetic stir bar inside.
[0058] 4. Place the glass vial from step 3 on a magnetic stirrer in a nitrogen glove box and stir at room temperature for 12 hours until all the solute is dissolved to obtain 1 mol / L Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 ) 33 Precursor solution;
[0059] 5. Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. The precursor solution was placed on a preheated hot plate (80°C) and left to stand for 2 hours until black perovskite seed crystals grew in the solution.
[0060] 6. Select small seed crystals with regular shape and both upper and lower surfaces being regular hexagons (approximately 0.1cm in side length and 0.05cm in thickness), and transfer them to the newly configured Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3. The precursor solution was placed in a preheated hot plate (65℃) and heated at a rate of 0.5℃ / h for 25h until Cs with regular shape and regular hexagonal shape on both the upper and lower surfaces (side length of the upper and lower surfaces is about 0.6cm and thickness is about 0.3cm) grew. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite single crystal;
[0061] 7. Transfer the grown Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Remove the perovskite single crystal from the glass bottle and subject the upper surface of the single crystal to ozone passivation treatment for 15 minutes.
[0062] 8. C is deposited on the ozone passivation side of the single crystal using physical vapor deposition. 60 A transport layer, a BCP transport layer, and a Cu electrode are deposited on the other side of the single crystal. A MoO3 transport layer and an Au electrode are then deposited, resulting in an X-ray detector based on a perovskite single crystal. 60 The thickness of the transport layer is 20 nm, the thickness of the BCP transport layer is 8 nm, the thickness of the Cu electrode is 90 nm, the thickness of the MoO3 transport layer is 25 nm, and the thickness of the Au electrode is 20 nm.
[0063] Example 4:
[0064] The method for fabricating a perovskite single-crystal X-ray detector provided by this invention includes the following steps:
[0065] 1. Clean the 5mL glass vial and magnetic stir bar sequentially with acetone, ethanol and deionized water using ultrasonic cleaning for 20min, and then dry them in an oven at 70℃ for 3.5h to obtain a dry and clean glass vial and magnetic stir bar.
[0066] 2. At room temperature, weigh out solid powders of FAI, PbI2, PbBr2, CsI and GAI in a molar ratio of 17:17:3:2:1 and add them to a sealed glass vial; the molar amount of FAI is 1.7 mmol.
[0067] 3. Add 2 mL of γ-butyrolactone (GBL) solvent to the glass vial from step 2, and place a magnetic stir bar inside.
[0068] 4. At room temperature, weigh out PCBM and C in a molar ratio of 1:1. 60 The solid powder was added to another sealed glass vial; the dosage of PCBM was 20 mg.
[0069] 5. Add 1 mL of dichlorobenzene (DCB) solvent to the glass vial from step 4, and place a magnetic stir bar inside.
[0070] 6. Place the glass vials from steps 3 and 5 on a magnetic stirring table in a nitrogen glove box and stir at room temperature for 12 hours until all the solute is dissolved to obtain 1 mol / L Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 ) 33 Precursor solution and 20 mg / mL PCBM: C 60 Solution;
[0071] 7. Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br0.1 )3. The precursor solution was placed on a preheated hot plate (80°C) and left to stand for 2 hours until black perovskite seed crystals grew in the solution.
[0072] 8. Select small seed crystals with regular shape and both upper and lower surfaces being regular hexagons (approximately 0.1cm in side length and 0.05cm in thickness), and transfer them to the newly configured Cs. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3. The precursor solution was placed in a preheated hot plate (65℃) and heated at a rate of 0.5℃ / h for 25h until Cs with regular shape and regular hexagonal shape on both the upper and lower surfaces (side length of the upper and lower surfaces is about 0.6cm and thickness is about 0.3cm) grew. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite single crystal;
[0073] 9. Transfer the grown Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Remove the perovskite single crystal from the glass bottle and subject the upper surface of the single crystal to ozone passivation treatment for 15 minutes.
[0074] 10. Transfer it to a nitrogen glove box, and add 65 μL of PCBM:C dropwise to the single-crystal ozone passivation treatment side each time. 60 The (1:1 molar ratio) solution was added dropwise 4 times. After the drop coating was completed, it was placed on a hot plate at 100°C for annealing for 1 hour.
[0075] 11. Using physical vapor deposition (PVD) on PCBM: C 60 A BCP transport layer and a Cu electrode are deposited on one side of the single crystal, and a MoO3 transport layer and an Au electrode are deposited on the other side, thus obtaining an X-ray detector based on a perovskite single crystal. The thickness of the BCP transport layer is 8 nm, the thickness of the Cu electrode is 90 nm, the thickness of the MoO3 transport layer is 25 nm, and the thickness of the Au electrode is 20 nm.
Claims
1. An X-ray detector based on dopant-induced formamidinium perovskite single crystal and its fabrication method, comprising the following steps: (I) Preparation of GAI-doped formamidinium perovskite single crystals 1) Preparation of Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 3. Solution: Mix solid powders of FAI, PbI2, PbBr2, CsI, and GAI in a molar ratio of 17:17:3:2:1 and dissolve them in 1–2 mL of γ-butyrolactone. Then, magnetically stir at room temperature until the perovskite material is completely dissolved to obtain CsI solution with a concentration of 0.5–2 mol / L. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite precursor solution; 2) Seed crystal growth: The Cs obtained in step 1) 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. After heating the perovskite precursor solution, maintain the temperature for a period of time until black perovskite seed crystals are formed in the solution. 3) Single crystal growth: The relatively regularly shaped perovskite seed crystal obtained in step 2) is transferred into the newly prepared and preheated Cs crystal as described in step 1). 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. In the perovskite precursor solution, the temperature is increased from the initial temperature of 60-65℃ for 15-30 hours to continue crystal growth, thereby obtaining Cs with regular shape and appropriate size. 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3 Perovskite single crystal; (II) Fabrication of GAI-doped formamidinium perovskite single-crystal X-ray detectors Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Ozone passivation treatment was performed on one side of the perovskite single crystal for 10-15 minutes; then, it was transferred to a nitrogen glove box, and PCBM:C was added dropwise to the ozone passivation side at a molar ratio of 1:
1. 60 The solution was added dropwise repeatedly 3–5 times; after the drop coating was completed, the perovskite single crystal was annealed on a hot plate at 90–110℃ for 0.5–2.0 h; finally, the obtained PCBM: C 60 A BCP transport layer and a Cu electrode are sequentially deposited on the transport layer, and a MoO3 transport layer and an Au electrode are sequentially deposited on the other side of the perovskite single crystal, thus obtaining an X-ray detector based on a perovskite single crystal.
2. The method for fabricating an X-ray detector based on a dopant-induced formamidinium perovskite single crystal as described in claim 1, characterized in that: The stirring time in step 1) is 8 to 12 hours.
3. The method for fabricating an X-ray detector based on a dopant-induced formamidinium perovskite single crystal as described in claim 1, characterized in that: Step 2) involves Cs 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Heat the solution to 80-85℃.
4. The method for fabricating an X-ray detector based on a dopant-induced formamidinium perovskite single crystal as described in claim 1, characterized in that: The heating rate in step 3) is 0.25–0.75 °C / h.
5. The method for fabricating an X-ray detector based on a dopant-induced formamidinium perovskite single crystal as described in claim 1, characterized in that: The thickness of the BCP transport layer is 8–10 nm, the thickness of the Cu electrode is 80–100 nm, the thickness of the MoO3 transport layer is 20–30 nm, and the thickness of the Au electrode is 18–22 nm.
6. The method for fabricating an X-ray detector based on a dopant-induced formamidinium perovskite single crystal as described in claim 1, characterized in that: Cs with regular shape and appropriate size 0.1 FA 0.85 GA 0.05 Pb(I 0.9 Br 0.1 )3. Perovskite single crystals have a regular hexagonal structure, with side lengths of 0.4–0.6 cm on the upper and lower surfaces and a thickness of 0.2–0.3 cm; Each time, add PCBM:C at a molar ratio of 1:
1. 60 The solution volume is 60–70 μL; PCBM: C 60 The solvent for the solution is dichlorobenzene, and the concentration range of PCBM is 15–30 mg / mL.
7. An X-ray detector based on a dopant-based formamidinium perovskite single crystal, characterized in that: It is prepared by the method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Titanate interfacial layers in perovskite material devices
CN108124492A
Hybrid perovskite material processing
CN110637255A